Evaluasi Implementasi Kurikulum Merdeka: Studi Literatur Mengenai Dampak terhadap Motivasi dan Hasil Belajar Siswa - Rima Pratiwi; Dewi Khosmawati; Jalaludin Jalaludin (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This study aims to evaluate the implementation of the Merdeka Curriculum policy by analyzing its impact on student motivation and learning outcomes. This research uses a systematic literature review method with a qualitative approach. Data were collected from various empirical research articles published between 2022-2025, examining the curriculum's application in primary and secondary education. The data were analyzed using thematic content analysis. The main synthesis results show that the implementation of the Merdeka Curriculum, particularly through Project-Based Learning (P5) and differentiated learning, consistently has a positive and significant impact on increasing student motivation, independence, and active participation. Various studies also confirm an improvement in student learning outcomes, both cognitively and in 21st-century skills. The most frequently reported primary challenges are teacher readiness, administrative load, and limited supporting facilities. It is concluded that the Merdeka Curriculum is effective in improving motivation and learning outcomes, but its uniform implementation success is highly dependent on systematic support for teacher training and infrastructure fulfilment.